Awareness of medical students about standard isolation precautions In Sulaimani City - M. Ali, Bushra; A. Mohammed, Saman; Tayb Abdullah, Balen; Muhammed, Osama; Fabian, Mutasam; Rauf, Muhammed (Kurdistan Journal of Applied Research, 2019)
The objectives of this study are to assess knowledge, Attitude and practice of medical students about standard isolation precautions and different college students and to identify those who vaccinated with HBV vaccine. A cross-sectional study was conducted from 27th of February 2019 till 1st of March 2019 in Sulaimani University among medical students .A convenient sample of 401 students were participated. Data was collected via online, entered by excel program and analyzed by SPSS program version 21. Chi-square test used to get the association, P value which is equal or less than 0.05 was regarded statistically significant. Majority of medical students had accepted knowledge (67 %), their attitude was positive (70 %), and had low practice (35 %). Most of the students answered wrongly regarding gloves should be worn if they attached to mucous membrane or non-intact skin and the highest percentage was among nursing college (85.3%), there was a significant association regarding P value (0.035).Most of the students believed that all health providers are at risk of occupational infections (75.6%), and the highest percentage was among nursing college (94.1%) and there was a significant association regarding P value (0.006). The percentage of the students that have taken a vaccine for Hepatitis B is (56.4%). Most of students had good knowledge regarding all aspects of Isolation Precaution, they had appropriate attitude toward it, high rate of medical students were lacking practice regarding the subject, in average college of Nursing had highest rate of all correct answers, About half of medical students have taken a vaccine for Hepatitis B.